2014
DOI: 10.1615/jenvironpatholtoxicoloncol.2014010179
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Subacute Pulmonary Toxicity Caused by a Single Intratracheal Instillation of Colloidal Silver Nanoparticles in Mice: Pathobiological Changes and Metallothionein Responses

Abstract: To study the acute and subacute pulmonary toxicity of colloidal silver nanoparticles (Ag-NPs), 0 or 100 ppm of Ag-NPs were instilled intratracheally in mice. Cellular and biochemical parameters in bronchoalveolar lavage fluid (BALF) and histological alterations were determined 1, 3, 7, 15, and 30 days after instillation. Ag-NPs induced moderate pulmonary inflammation and injury on BALF indices during the acute period; however, these changes gradually regressed in a time-dependent manner. Concomitant histopatho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 0 publications
3
20
0
Order By: Relevance
“…A recent report showed that AgNP intratracheal instillation could cause acute and subacute pulmonary toxicity in mice at dosage of 1 mg/g body weight [34]. At a lower dosage of 0.5 mg/g body weight, AgNP treatment upregulated the secretion of proinflammatory cytokines and influenced the gene expression profile of lung tissue, but histopathological changes in the lung were only observed at day 1 after instillation [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent report showed that AgNP intratracheal instillation could cause acute and subacute pulmonary toxicity in mice at dosage of 1 mg/g body weight [34]. At a lower dosage of 0.5 mg/g body weight, AgNP treatment upregulated the secretion of proinflammatory cytokines and influenced the gene expression profile of lung tissue, but histopathological changes in the lung were only observed at day 1 after instillation [35].…”
Section: Discussionmentioning
confidence: 99%
“…The lung and the trachea are the direct targets of the damage after acute exposure by intratracheal instillation. Lung inflammation and tissue damage are two main outcomes due to the local high concentrations attained in the lung [34,38]. Two major routes may be involved in the damage in peripheral organs.…”
Section: Discussionmentioning
confidence: 99%
“…70 In this case, exposure to AgNPs induced 5-fold increase of mRNA level of MTs at 12 h and 10-fold at 24 h, in accordance with other reports. 61,62,71,72 Binding of silver to MTs was indirectly supported by changes in the secondary structures of MT by circular dichroism (CD) spectra ( Figure 7C and Table 2). Cysteine residues in MTs were bound to I dissolved silver to form AgÀSÀ bonds as indicated by Ag L 3 -edge XANES spectra ( Figure 7D).…”
Section: Articlementioning
confidence: 92%
“…It has been shown that expression of MTs is induced in inflammatory lung diseases (Inoue et al, 2008); Kaewamatawong et al (2014) demonstrated the expression of MTs after lung exposure to colloidal Ag ENPs in mice. In a previous study, we showed the inflammatory effects of pulmonary administered Ag ENPs, the same ENPs as used in this study, with infiltration of neutrophils and expression of the pro-inflammatory cytokine IL-1b (Smulders et al, 2014), a known inducer of MT gene expression (De et al, 1990).…”
Section: Elementmentioning
confidence: 99%